PEMANFAATAN DAUN KIPAHIT (Tithonia diversifolia) SEBAGAI ALTERNATIF PENGENDALIAN HAMA KEONG MAS (Pomacea canaliculata L.) PADA TANAMAN PADI. - Tri Bagus Wicaksono; Saifuddin Hasjim; Nanang Tri Haryadi (Universitas Trilogi, 2019)
Golden snail (Pomacea canaliculata L.) is one of the main pests that attack young paddy plants. Golden snail pest attack on paddy plants has the potential to reduce yields and even crop failure. Kipahit plants (T. diversifolia) have the potential as bio molluscides because they contain toxic compounds against golden snails. The purpose of this research was to study the effect of bio molluscicide concentration of kipahit leaf extract (T.diversifolia) on mortality of golden snails at two phases of age and damage intensity of paddy plants. The. The research was conducted in December 2017 until May 2018. The research was carried out in Lampeji Village, Mumbulsari District, Jember Regency. The researh used a Completely Randomized Design (CRD) with 6 concentrations of kipahit leaf extract, tested on 2 different age phases of golden snail and 3 times repeated. The variables observed were golden snail mortality, crop damage intensity (DI), Lethal Concentration 50 (LC50) and Lethal Time 50 (LT50). The data obtained were then analyzed by probit analysis and Duncan test with a confidence level of 95%. The results showed that the concentration of 60 g/L was the most efficient and effective concentration in controlling golden snails at various age phases as well as suppressing the intensity of damage to paddy plants. Keywords: golden snail, kipahit leaves (T. diversifolia), molluscicide, mortality